Towards an understanding of the burdens of medication management affecting older people: the MEMORABLE realist synthesis - Maidment, I; Lawson, S; Wong, G; Booth, A; Watson, A; Zaman, H; Mullan, J; McKeown, J; Bailey, S (BMC, 2020)
Background More older people are living in the community with multiple diagnoses and medications. Managing multiple medications produces issues of unrivalled complexity for those involved. Despite increasing literature on the subject, gaps remain in understanding how, why and for whom complex medication management works, and therefore how best to improve practice and outcomes. MEMORABLE, MEdication Management in Older people: Realist Approaches Based on Literature and Evaluation, aimed to address these gaps.